TRANSFORMASI DIGITAL DALAM INDUSTRI DISTRIBUSI BAHAN BANGUNAN: Studi Kasus: Uji Kepuasan Platform B2B pada PT. Bumi Pembangunan Pertiwi di Kab. Madiun, Jawa Timur - Pradana, Mares; Shiddiqi, Ary Mazharuddin; Triyono, Budi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Digital transformation has become an urgent necessity for companies to remain competitive in the rapidly advancing digital era. Through digitalization, businesses can enhance efficiency, competitiveness, and sustainability by automating processes, reducing errors, and providing accurate real-time data for better decision-making. However, the adoption of digital technology varies across different sectors, with the building materials distribution sector lagging behind. PT. Bumi Pembangunan Pertiwi, part of Success Jaya Distribution, which operates in building materials distribution sector in East Java, still relies on manual processes in its operations. Observations and interviews reveal that key activities such as the creation of historical data reports, inventory management, billing, and approvals are still handled manually. This situation negatively impacts the efficiency and accuracy of the company’s operations. Key issues identified include a lack of well-documented historical data, inconsistencies in inventory management, slow and error-prone billing processes, and time-consuming approval procedures. Additionally, excessive paper usage contributes to inefficiencies and environmental harm. Digitizing business processes through the development of a Business to Business (B2B) platform offers a solution to enhance operational efficiency, transparency, and business sustainability. The implementation of this platform is expected to address the challenges faced by PT. Bumi Pembangunan Pertiwi and improve the performance of other building materials distributors in the digital era.The evaluation results showed a very good level of user satisfaction with a total CSI of 84.42%, where the components of User Experience, Satisfaction with Process and Output, and General Satisfaction were respectively 25.64%, 34.52%, and 24.25%.